Answer:
y =
Step-by-step explanation:
Let the equation of the line is,
y = mx + b
m = Slope of the line
b = y-intercept
Since, slope of a line passing through two points
and
is given by,
m = ![\frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
Since, the given line passes through two points (-5, 1) and (4, -2)
Slope of the line 'm' =
= ![-\frac{1}{3}](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B3%7D)
Equation of the line will be,
y = ![-\frac{1}{3}x+b](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B3%7Dx%2Bb)
Since, this line passes through (4, -2),
-2 = ![-\frac{4}{3}+b](https://tex.z-dn.net/?f=-%5Cfrac%7B4%7D%7B3%7D%2Bb)
b = ![\frac{4}{3}-2](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7D-2)
b = ![-\frac{2}{3}](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7B3%7D)
Therefore, equation of the line will be,
y =